2006
DOI: 10.1016/j.ejcts.2006.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Reduced myocardial expression of calcium handling protein in patients with severe chronic mitral regurgitation☆☆☆

Abstract: In chronic volume overload the down-regulation of SERCA2a and 2b at the mRNA and SERCA2 protein levels exist. Moreover, protein levels of SERCA2 tend to correlate to the grade of left ventricular diastolic dilatation and suggest an important role LV remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Nevertheless, the marked lipofuscin accumulation and myofibrillar degeneration in LV endomyocardial biopsies are indeed markers of heart failure that were present in patients with otherwise normal LV strain rates and LVEF prior to surgery. This underscores the unreliability of ejection phase indices in reflecting underlying LV myocardial damage on ours and other studies (810). These findings may be of use in defining the optimal timing of mitral valve surgery.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Nevertheless, the marked lipofuscin accumulation and myofibrillar degeneration in LV endomyocardial biopsies are indeed markers of heart failure that were present in patients with otherwise normal LV strain rates and LVEF prior to surgery. This underscores the unreliability of ejection phase indices in reflecting underlying LV myocardial damage on ours and other studies (810). These findings may be of use in defining the optimal timing of mitral valve surgery.…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies in patients with isolated MR and LVEF > 55% have demonstrated decreases in the force-frequency effect in isolated LV muscle strips (9) and in LV calcium handling proteins (8), indicative of mechanical and biochemical markers of heart failure. In another study, LV TNF-α was increased in patients with isolated MR and well preserved LVEF (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is of interest that previous studies report that in patients with isolated MR, who largely present in Class III to IV heart failure, there is a down regulation of SERCA2a LV protein levels and a negative correlation between SERCA2a protein levels and LV end-diastolic diameter. 10,11 Thus, as with the failing heart, the decompensated MR heart has decreased SERCA2a expression, whereas in our patients who largely presented in Class I and II symptoms, β-adrenergic signaling is increased and SERCA2a mRNA and protein expression is unchanged at this earlier stage in isolated MR.…”
Section: Discussionmentioning
confidence: 49%
“…To quantify the expression of the KA1 subunit and GAPDH, the PCR products were analyzed using the density-metric program (Multi Gauge) of a Las-3000 image analyzer (Fuji, Japan) after gel scanning with Gel-Doc 1000 (Bio-Rad, Italy). The expression density of the KA1 subunit PCR products was normalized against GAPDH [9,21,43]. The normalized data of each group (juvenile KA1/GAPDH, prepubescent KA1/GAPDH and adult KA1/GAPDH) were renormalized according to the juvenile density of each group.…”
Section: Methodsmentioning
confidence: 99%